2001
DOI: 10.1186/ar387
|View full text |Cite
|
Sign up to set email alerts
|

Body mass indices in patients with disabling hip osteoarthritis

Abstract: Hip osteoarthritis (OA) is a degenerative joint disease that results in substantial morbidity. The disease may be preventable in some instances by reducing risk factors associated with the disease. We undertook a study to determine whether being overweight or obese, a health risk that applies to younger and older age groups, is commonly associated with hip joint OA. The body mass indices (BMIs) of 1021 males and females ranging in age from 23 to 94 years and requiring surgery for end-stage hip joint OA were an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(9 citation statements)
references
References 25 publications
0
7
0
2
Order By: Relevance
“…59, 73, 92, 95, 117 The most current evidence shows BMI is not related to hip OA. 161 What seems apparent is that obesity is probably associated with the progression of hip OA rather than onset, 127 and the therapeutic value of weight loss is important. 52, 202 …”
Section: Clinical Guidelinesmentioning
confidence: 99%
“…59, 73, 92, 95, 117 The most current evidence shows BMI is not related to hip OA. 161 What seems apparent is that obesity is probably associated with the progression of hip OA rather than onset, 127 and the therapeutic value of weight loss is important. 52, 202 …”
Section: Clinical Guidelinesmentioning
confidence: 99%
“…The potential role of leptin in OA is supported by the relationship between high body mass index and an increased risk of OA [19]. Leptin has been detected also in synovial fluid obtained from patients with OA [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…In relation to higher BMI among patients who are candidates for hip arthroplasty, some studies have correlated hip osteoarthrosis with obesity. 10 , 11 It has been observed that the great majority of the patients who are candidates for THA are outside of this ideal weight range.…”
Section: Discussionmentioning
confidence: 99%